Relationship between Body Image and Dietary Status with Anemia in Adolelescent girl in Dusun III Bakaran Batu Village Batang Kuis District Deli Serdang Regency - Rina Marlina Hutasuhut (Institute of Computer Science (IOCS), 2022)
Anemia is a body condition in which the level of hemoglobin (Hb) in the blood is lower than normal. Hemoglobin is one of the components in red blood cells/erythrocytes that functions to bind oxygen and deliver it to all body tissue cells. Adolescent girls are susceptible to malnutrition during the second peak period of growth and development, lack of nutrient intake due to wrong eating patterns, the influence of the social environment (wanting to be slim). Adolescent girls who are malnourished cannot achieve optimal nutritional status (thin, short and disproportionate bone growth). Lack of iron and other nutrients that are important for growth and development (zinc), often getting sick. The purpose of this study was to determine anemia in adolescent girls in hamlet III, Bakaran Batu village, Batang Kuis sub-district, this type of research was descriptive analytic which aims to describe the relationship between body image, diet status and anemia in adolescent girls in hamlet III. This research was conducted from January to July, the research population was 65 respondents and the population was sampled using total sampling with research instruments, namely questionnaires and digital HB checks. Management of data by editing, coding, tabulating and data entry the results of the majority of the research are anemia as many as 52 respondents (80.0%), the majority of respondents with negative body image 51 respondents (78.5%), the results of the study of the relationship between body image and anemia obtained (OR) = 40,000. 95% CI = 7,723-207,178 and P value 0.000 <0.05, the relationship between diet status and anemia was obtained (OR) = 36.750. 95% CI = 7.008-192.726 and P value 0.000 <0.05. Teenagers to further increase knowledge about anemia, body image and healthy diet by consuming balanced nutrition and respecting body image so that they can become productive and healthy teenagers.